Early modern catalogues of imaginary books
1 online resource.
Keywords: For this bilingual (English-French) anthology of early modern fictitious catalogues, selections were made from a multitude of texts, from the genre’s beginnings (Rabelais’s satirical catalogue of the Library of St.-Victor (1532)) to its French and Dutch specimens from around 1700. In thirteen chapters, written by specialists in the field, diverse texts containing fictitious booklists are presented and contextualized. Several of these texts are well known (by authors such as Fischart, Doni, and Le Noble), others – undeservedly – are less known, or even unrecorded. The anthology is preceded by a literary historical and theoretical introduction addressing the parodic and satirical aspects of the genre, and its relationship to other genres: theatre, novel, and pamphlet. Contributors: Helwi Blom, Tobias Bulang, Raphaël Cappellen, Ronnie Ferguson, Dirk Geirnaert, Jelle Koopmans, Marijke Meijer Drees, Claudine Nédelec, Patrizia Pellizzari, Anne-Pascale Pouey-Mounou, Paul J. Smith, and Dirk Werle.